ENGLISH ROLE PLAY SIMULATION TRAINING FOR HOSPITAL EMERGENCY ROOM STAFF AT RS MITRA HUSADA PRINGSEWU - Fini Widya Fransiska; Esa Pratama Putra (Jurnal Pengabdian Masyarakat, 2025)
Communication effectiveness in the Emergency Room (ER) has a direct correlation with patient safety, particularly when dealing with international patients. However, medical staff at RS Mitra Husada Pringsewu still face English language barriers that trigger low self-confidence and the risk of misdiagnosis. This community engagement activity aims to enhance the communicative and procedural competence of ER staff through measured role-play simulation training. By adopting the Participatory Action Learning (PAL) framework and David Kolb’s Experiential Learning theory, 25 ER staff members were involved in realistic clinical scenario simulations, ranging from the triage stage to emergency procedures. Evaluation results indicate a significant increase in the staff's average English competency score, rising from 54.5 in the pre-test to 82.3 in the post-test. The most substantial improvements were recorded in medical vocabulary mastery and speaking fluency in emergency situations. Beyond linguistic aspects, this training successfully reduced foreign language anxiety and improved the staff's ability to apply politeness strategies and empathy toward patients. Based on these results, it is recommended that the hospital develop bilingual SOPs and establish independent study groups to ensure the sustainability of staff competence in providing international-standard healthcare services.